1998
DOI: 10.1046/j.1365-313x.1998.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Six Arabidopsis thaliana homologues of the human respiratory burst oxidase (gp91phox)

Abstract: SummaryAn NADPH oxidase analogous to that in mammalian phagocytes has been hypothesized to produce reactive oxygen species (ROS) in the plant defence response. A. thaliana contains at least six gp91 phox homologues, designated AtrbohA-F (A. thaliana Respiratory Burst Oxidase Homologues), which map to different positions. Transcripts of three of these genes can be detected in healthy plants by RNA gel blot analyses. The Atrboh gene products are closely related to gp91 phox and the intron locations suggest a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
223
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(232 citation statements)
references
References 17 publications
8
223
0
1
Order By: Relevance
“…Plasma membrane NADPH oxidases in plants have been discovered on the basis of their sequence similarity to the mammalian respiratory burst NADPH oxidase subunit gp91 phox (Groom et al, 1996;Keller et al, 1998;Torres et al, 1998). They are encoded by a 10-member gene family in Arabidopsis (Arabidopsis thaliana; rbohA to rbohJ, for respiratory burst oxidase homolog).…”
mentioning
confidence: 99%
“…Plasma membrane NADPH oxidases in plants have been discovered on the basis of their sequence similarity to the mammalian respiratory burst NADPH oxidase subunit gp91 phox (Groom et al, 1996;Keller et al, 1998;Torres et al, 1998). They are encoded by a 10-member gene family in Arabidopsis (Arabidopsis thaliana; rbohA to rbohJ, for respiratory burst oxidase homolog).…”
mentioning
confidence: 99%
“…Molecular studies revealed some similarities and differences between the mechanisms regulating NADPH oxidases in plants and animals. Although homologs of the gp91 phox catalytic subunit of the neutrophil NADPH oxidase (Keller et al, 1998;Torres et al, 1998) and putative homologs of the Rac small G protein regulatory subunit (Yang, 2002) Article, publication date, and citation information can be found at www.plantphysiol.org/cgi …”
mentioning
confidence: 99%
“…Homologs of gp91 phox have been identified in several plant species [90][91][92]. The Arabidopsis genome encodes ten putative gp91 phox homologs, termed Respiratory burst oxidase homolog (Rboh) [93].…”
Section: Regulation Of Nadph Oxidasementioning
confidence: 99%